ESTABLISHMENT OF SANTRI CHARACTERS THROUGH INCLUSIVE SOFT SKILL-BASED EXTRACURICULAR ACTIVITIES IN DAYAH DARUL IMAN ACEH TENGGARA - Syadidul Kahar (Journal of Education and Teaching Learning, 2022)
This article seeks to describe the phenomenon of students' moral formation through extracurricular activities based on inclusive soft skills. This study uses a qualitative method with a phenomenon approach in data collection and analysis. Based on the data analysis, it was found that Dayah Darul Iman made the dayah a forum for the formation of students' morals through role models by actualizing the spirit of inculcating Islamic values ??in various activities carried out by dayah teachers. The management of Dayah Darul Iman which is pursued by the leadership and all managers in general seeks to make Dayah Darul Iman a miniature of the community so that the alumni of Dayah are able to take part in the community. Inclusive-based soft skills extracurricular activities at Dayah Darul Iman include greetings, smiles, greetings and family activities; the culture of each activity; the culture of reading prayers when starting and ending study; disciplined culture; and clean culture; honest culture; and a culture of shame when lying and arriving late, and a culture of playing an active role in protecting the environment and every activity. During the leadership of Abuya Bukhari Husni, dayah has implemented a curriculum by combining general education, the yellow book and inclusive soft skills extracurriculars. This change is due to the social demands of the people of Southeast Aceh, which is a multicultural society. On the other hand, Southeast Aceh is on the border with North Sumatra, so the flow of information moves quickly and varies.